Attitude of university students to extracurricular activities - Valero Ancco, Vidnay Noel (2021)
The objective was to determine students' attitudes to the extracurricular activities of the Professional School of Primary Education of the National University of Altiplano during 2019. It is a non-experimental research with descriptive explanatory design, the population was all students enrolled during the academic year 2019, the sample consisted of 60 students selected with a sampling of a non-probabilistic type. It is concluded that there is a good attitude of students to extracurricular activities, since the average participation is 71.63% of students. In addition, the main personal factor driving students' participation in the face of extracurricular activities is that they constitute for them a space that allows them to show their talents; and the main social factor is that they consider that by participating in them they can spend more time with their friends.